Efficient simulation of large-scale urban environment with adaptive multiple-scene management - Le, Minh Duc (2014)
Project sizes and complexities of 3D Games and Simulations have increased drastically during the last ten years. Nowadays, a large number of applications have increasing scene complexity with non-scene-boundaries and contain many types of objects, both outdoors and indoors. There is, however, no general scene management system that can efficiently handle all scene types. It is already a heavy burden to deal with each scene individually. It definitely becomes very challenging to handle the combination of multiple-scene types. Another challenge is the increasing complexity of Physics and Artificial Intelligence (AI) simulation. Optimization becomes harder especially when there are a lot of agents involved and when resources are limited. There are also too many high-level algorithmic choices that require years of experience to master and identify the most suitable algorithms for specific tasks.